Comparison of Dark Temporal Cavity Solitons in Fabry-Pérot and Ring Resonators with Normal Dispersion - Campbell, Graeme N.; Hill, Lewis; Del'Haye, Pascal; Oppo, Gian Luca (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Bright and dark temporal cavity solitons are of interest for the generation of highly stable optical frequency combs. Here we characterise dark temporal cavity solitons generated in a Fabry-Pérot (FP) resonator with normal dispersion and make comparison to their counterparts generated in ring resonator systems. We consider a high finesse FP resonator filled with a Kerr material and driven by linearly polarized light, see Fig. 1a. This system has been described in the anomalous dispersion regime in [1] where a so called FP Lugiato-Lefever equation has been derived and investigated. For normal dispersion this equation takes the form (equation presented) which describes the intracavity field ψ with input field S and detuning to the nearest cavity resonance θFP. Here t,ζ are the slow time and fast time variables describing the evolution over many round trips and single round trip tR respectively. The term with angled brackets corresponds to the average power of the field over a round trip of the resonator and arises from the inherent counterpropagation of intracavity fields in a FP configuration. Integral terms of this kind are also present in bidirectionally pumped ring resonators where, however, there are two coupled equations, one for each counterpropagating field [2,3].
CRIS-Team Scopus Importer:2024-12-16